'Fiddling with young kiddies' minds': reporting on the Safe Schools Coalition in Australia. Issue 3 (4th May 2019) - Carden, Clarissa
ABSTRACT: The Safe Schools Coalition Australia program provides resources, including information packages, training and an eight-lesson curriculum, intended to promote the understanding of LGBTI (lesbian, gay, bisexual, transgender and intersex) young people in Australian schools. This program has been controversial, with opposition enflamed in no small part by inaccurate rhetoric put forward by politicians and some media outlets which positions this anti-bullying program as a radical intervention into existing gender and sexual norms. In part due to the public outcry caused by such rhetoric, it has been defunded on a national level. This article explores the response of Queensland's only major print newspaper, The Courier Mail, to the introduction and subsequent use of this program in the state from mid-2015. This program has been characterized in this newspaper alternatively as a necessary intervention into existing school cultures and an undesirable act of social engineering. Using critical discourse analysis, I seek to explore these divergent viewpoints in light of broader debates relating to religion, social change and the role of schools in protecting children and producing good citizens. Fears of Marxism, changing gender norms and a perceived decline of Christian influence on state education are shown to be key factors in the negative coverage of this program.